SCHOOL NON-ATTENDANCE: A STUDY OF ITS CAUSES AMONG HICH SCHOOL STUDENTS IN MASVINGO DISTRICT SECONDARY SCHOOLS, ZIMBABWE - Simuforosa, Magwa; Rosemary, Ngara (IJRDO - Journal of Social Science and Humanities Research, 2016)
The progress of a nation is very much dependent on the education of its citizens. One major issue schools are facing and seeing little or no improvement with is effectively dealing with absenteeism. Learners should be in school all the times for them to acquire and keep concepts taught.This qualitative studyaimed to explore the factors that lead to learner non-attendance in high schools. The case study design was employed since it is an in-depth study of a district within its real life context. Data was collected using questionnaires with 20 teachers and 10 learners.Interviews with 10 students and 10 teachers from high schools in Masvingo urban schools were held to establish factors which lead to school non-attendance among secondary school learners. The participants were purposively selected. The collected data established that risk factors associated withlearner absenteeism can be grouped into four main categories. It was discovered that the factors leading to school absenteeism emanate from the family, the school, the individual child and community. Under each of the four categories, various aspects related to the category were discussed. From these findings, the study recommends that parents should understand their responsibilities and be involved in their children’s work. Furthermore, schools should make efforts to involve parents to monitor their children’s absence and create friendly atmosphere for learners. The study also recommends future research on effects of absenteeism on student’s academic performance.